Efektivitas Terapi Akupresur Terhadap Nyeri (Dismenore) Pada Remaja - Martina Danta Sastriani; Oswati Hasanah; Sri Wahyuni (STIKes Payung Negeri Pekanbaru, 2022)
Aim: This study was conducted to determine the effectiveness of acupressure therapy on dysmenorrhea pain in adolescents Method: This study used a quasy experimental design with pre-test and post-test forms. The location of this research was conducted on students in a faculty in a university in Pekanbaru with a total sample size of 32 respondents who were selected based on the inclusion and exclusion criteria set by the researcher, while the inclusion criteria in this study were respondents aged 18-22 years. , pain felt on the first day with a pain intensity of 4-9 (NRS scale), and did not use analgesic drugs while the exclusion criteria in this study were pain intensity 10 (based on NRS) Conclusion: Acupressure therapy is very effective in reducing dysmenorrhea pain and can be used as a non-pharmacological alternative treatment to treat dysmenorrhea.